The Effect of The Eracs Sectio Caesaria Method on Early Mobilization in Mothers Post-Sectio Caesaria - Sudiniasih; Ellyzabeth Sukmawati; Qomariyah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Caesarean section (CS) is a major surgical procedure frequently performed for childbirth with specific medical indications. Early mobilization after CS is crucial to accelerate recovery and prevent complications. The Enhanced Recovery After Caesarean Surgery (ERACS) method is a modern approach aimed at enhancing recovery through multimodal pain management and early mobilization. This study aimed to investigate the effect of the ERACS method on early mobilization in post-caesarean section mothers. This research employed a quantitative design with a one-group post-test only approach. The study population comprised postpartum mothers following CS at Islamic Hospital (RSI) Al-Ikhlas Pemalang. A total of 50 respondents were selected using purposive sampling. Data were collected using observation sheets and analysed using a one-sample t-test. The results showed that the majority of respondents (78%) achieved independent early mobilization, with a statistically significant p-value of 0.000, indicating a meaningful effect. This study consists of viii (8) pages of introduction, 72 pages of main discussion, 5 data tables, 2 conceptual framework diagrams, and 8 supporting appendices. In conclusion, the ERACS method has a positive effect on early mobilization in post-caesarean section mothers.